Severe back pain – risk factors. Issue 15 (10th November 2011) - Akhtar, M A; Clark, A; Atiya, S; Chirputkar, K; Ayana, G; Smith, S
Abstract : Back pain is a common problem in all age groups. Different risk factors have been identified including high BMI, Smoking, alcohol, and psychological history. The aim of our study was to identify if there was a difference in the incidence of these risk factors in different age groups. We collected data prospectively for 26 consecutive patients admitted between January and March 2011 with severe back pain who needed an MRI scan to rule out Cauda equina syndrome or nerve root compression in a district general hospital. Demographic details were recorded along with their occupation, BMI, Smoking status, alcohol intake and psychological history. Group A (Younger Group) had 13 patients with a mean age of 38 y (range 29–44). 7 (54%) were female and 6 (46%) male. 6 (46%) were employed, 4 (30%) unemployed and 2 (15%) housewives. The mean BMI was 29 (range 24–40). 7 patients (54%) were smokers and alcohol users and 6 (46%) were non-smoker and non-alcohol users. 5 patients (38%) had associated psychological history. Group B (Older group) had 13 patients with a mean age of 59 years (range 45–79). 11 (85%) were female and 2 (15%) male. 5 (38%) were employed, 2 (15%) retired and 3 (23%) house-wives. The mean BMI was 21 (range-14–32). 6 patients (46%) were smoker and 7 (54%) enjoyed alcohol. Only 2 patients (15%) had associated psychological history. Younger patients with severe back pain were overweight (mean BMI-29) and had higher incidence of psychological history (38%) as compared to older patients (15%). There was no difference in the occupation status, smoking and alcohol consumption in both groups. Younger patients with severe back pain should be routinely assessed for associated psychological history and appropriate advice on weight management should be given.